Status and trends of performance of commercial engines in the Philippines - Eusebio, Romulo E.; Suministrado, Delfin C.; Aranguren, Darwin C.
AMTEC have tested 476 various engines from 1982 to 2009 with power rating of at most 18.7 kw (25 hp). These consisted of gasoline (35.3 percent), air-cooled diesel (16.8 percent) and water-cooled diesel engines (47.9 percent). The engines were imported from different countries with the most number coming from China (23.7 percent), followed by Japan (18.9 percent) and Thailand (10.3 percent). The rest came from Vietnam (7.77 percent), Taiwan (7.56 percent), India (6.30 percent), Korea (6.09 percent), U.S.A. (5.67 percent), Indonesia (5.67 percent), Italy (4.62 percent), Germany (2.10 percent) and Mexico (1.26 percent). In terms of performance, the gasoline engines and air-cooled diesel engines from Japan, and the water-cooled diesel engines from Vietnam, Indonesia and Thailand showed high rating. All the three kinds of engines from China performed poorly. In comparison among engine types, water-cooled engines have higher performance rating, followed by air-cooled engines and gasoline engines.
Keywords: Engines; Engine performance; AMTEC test